2017
DOI: 10.1002/2017ja024211
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous observations of magnetospheric ELF/VLF emissions in Canada, Finland, and Antarctica

Abstract: To investigate longitudinal extent of electromagnetic wave activity, we report the first simultaneous ground‐based observations of magnetospheric ELF/VLF emissions at the following three longitudinally separated stations at auroral and subauroral latitudes: Athabasca, Canada (ATH; magnetic latitude: 61.3°N); Kannuslehto, Finland (KAN; 64.4°N); and Syowa Station, Antarctica (SYO; 70.5°S). The magnetic local time (MLT) separations of SYO‐KAN, ATH‐SYO, and ATH‐KAN, are 3, 8, and 11 h, respectively. Simultaneous o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…This supports the dawn-dusk asymmetry which also holds for observations of many whistler mode wave phenomena (e.g., Walsh et al 2014, and references herein). Previous statistical studies of ground-based observations are consistent with this conclusion (e.g., Golden et al 2011;Yonezu et al 2017). The results further indicate that the variability of the dawn side intensities is larger than the variability of the dusk side intensities, as the higher principal components do not seem to be related with the dusk local time sector (not shown).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This supports the dawn-dusk asymmetry which also holds for observations of many whistler mode wave phenomena (e.g., Walsh et al 2014, and references herein). Previous statistical studies of ground-based observations are consistent with this conclusion (e.g., Golden et al 2011;Yonezu et al 2017). The results further indicate that the variability of the dawn side intensities is larger than the variability of the dusk side intensities, as the higher principal components do not seem to be related with the dusk local time sector (not shown).…”
Section: Discussionsupporting
confidence: 85%
“…Both types of emissions were predominantly observed during winter months rather than during summer season. Yonezu et al (2017) reported a statistical analysis of measurements from three different ELF/VLF groundbased stations (Athabasca, Canada; Kannuslehto, Finland; Syowa, Antarctica). The results show that the simultaneous wave occurrence rate is higher in the dayside morning sector, suggesting possible MLT dependence of the wave longitudinal extent.…”
Section: Introductionmentioning
confidence: 99%
“…As shown by Ozaki et al (2008), the ELF/VLF waves expand only about 500 km from the exit point of the ionosphere to the ground, allowing the PWING stations to see the localization of the magnetospheric ELF/VLF waves. Recently Yonezu et al (2017) examined the simultaneous occurrence rate of the magnetospheric ELF/VLF emissions using 48-day loop antenna data obtained at ATH, KAN, and the Syowa station in Antarctica. These stations are separated in local times of 3, 8, and 11 h. The simultaneous occurrence rates are 9.8, 2.5, and 3.6% for SYO-KAN (3-h local time difference), ATH-SYO (8 h), and ATH-KAN (11 h), respectively.…”
Section: Frequency [Hz]mentioning
confidence: 99%
“…We calculated the wave occurrence rate by dividing the number of wave bins by the number of simultaneously available bins. These criteria are the same as those used by Martinez-Calderon et al (2015) and Yonezu et al (2017). Figure 3 shows the ELF/VLF wave occurrence rate at each station during the simultaneously available period.…”
Section: Data Definitionmentioning
confidence: 99%